"Be here now" – service users' experiences of a mindfulness group intervention - Wilson, Charlotte; Dillon, Aiveen; Jackman, Catherine (My University, 2018)
Purpose: The purpose of this paper is to explore service users’ experiences of a mindfulness group intervention. Design/methodology/approach: In total, 15 participants with a diagnosis of a mild or moderate intellectual disability and concurrent mental health difficulties were interviewed using semi-structured interviews about their experiences of attending the mindfulness group. Findings: Thematic analysis was used to interpret the data. The three super ordinate themes that emerged were positive aspects of mindfulness, positive aspects of attending the group and negative aspects of attending the group. There were seven subthemes. The results highlighted that participants found the mindfulness group to be beneficial, partly due to specific aspects of the mindfulness intervention and partly due to the group process. The negative aspects of the group were harder to elicit, and were less specifically related to mindfulness. Originality/value: Mindfulness-based interventions have emerged as a promising approach for individuals with intellectual disabilities with mental health difficulties. There is currently a lack of research exploring service users with intellectual disabilities about their experiences of mindfulness interventions.
PUBLISHED
Keywords: Mental health; Intellectual disabilities; Mindfulness; Groups; Thematic analysis; Qualitative; Inclusive Society; Mental health and intellectual disability; Mindfulness